Pendisiplinan Tubuh Laki-Laki Dalam Kontes Kebugaran Laki-Laki Internasional - Teguh Dwi Putranto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The appeal of the male body as a target for capitalism's exploitation rivals that of the female body, which is typically targeted by beauty pageants. The disciplined male body that uses fitness aids has now entered the male fitness competitions, one of which is Mister Supranational. One of the yearly international men's fitness competitions is now taking place in Poland. This study aims to demonstrate the male body's discipline in the Mister Supernational competition. In this study, Krippendorff content analysis was the methodology. The unit of analysis of this research is the photos of the list of Mister Supranational winners from 2016 to 2021. The results of the research show that the men body discipline in the Mister Supranational fitness contest was created with a beard men figure. This also reinforces that the masculine side of men is still shown through beards in a men fitness contest. Keywords: Body Discipline; Men Body; Fitness Contest; Mister Supranational.